Does Education Reduce CO2 Emmisions? Empirical Evidence of The Environmental Kuznets Curve in Indonesia - Umaroh, Rodhiah (Journal of Reviews on Global Economics, 2019)
The purpose of this study is to analyze whether education has a role in energy use in society using the Environmental Kuznets Curve (EKC) hypothesis during the period 1972-2016 in Indonesia. The paper applied the Autoregressive Distrubuted Lag (ARDL) Bound Test approach to identify co-integration relationships among variables in the model. The results confirmed the evidence that education initially increased CO2 emmisions and at some point education reduced co2 in the short run but not in the long run. In addition, i also found conclusive evidence to support the Inverted U-shaped EKC hypothesis of the relationship between GDP per capita and environmental degradation. The stability test has conducted in estimated model and the result indicated that estimated model is stable over time.